A Nice Geometry Problem (1)

Calculus Level 4

A circle of radius 1 is tangent to the parabola y = x 2 , y=x^2, as shown.

Find the gray area between the circle and the parabola.

If the area can be written as A A B π A , \dfrac{A\sqrt{A}}{B}-\dfrac{\pi}{A}, then what is A + B ? A+B?


The answer is 7.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Chew-Seong Cheong
May 28, 2018

Let the center of the unit circle be C ( 0 , c ) C(0,c) . Then, we have { ( y c ) 2 + x 2 = 1 Equation of the unit circle y = x 2 Equation of the parabola \begin{cases} (y-c)^2 + x^2 = 1 & \small \color{#3D99F6} \text{Equation of the unit circle} \\ y = x^2 & \small \color{#3D99F6} \text{Equation of the parabola} \end{cases} .

Considering x 0 x \ge 0 . The points which the circle and parabola intersect satisfy the two equation and:

( y c ) 2 + x 2 = 1 Since y = x 2 ( y c ) 2 + y = 1 y 2 ( 2 c 1 ) y + c 2 1 = 0 \begin{aligned} (y-c)^2 + {\color{#3D99F6} x^2} & = 1 & \small \color{#3D99F6} \text{Since }y = x^2 \\ (y-c)^2 + {\color{#3D99F6} y} & = 1 \\ y^2 - (2c-1)y + c^2 - 1 & = 0 \end{aligned}

Solving the quadratic equation for y y , y = 2 c 1 ± ( 2 c 1 ) 2 4 ( c 2 1 ) 2 = 2 c 1 ± 5 4 c 2 y = \dfrac {2c-1 \pm \sqrt{(2c-1)^2-4(c^2-1)}}2 = \dfrac {2c-1 \color{#3D99F6}\pm \sqrt{5-4c}}2 . For the circle to be tangent to the parabola or only 1 contact point 5 4 c = 0 \color{#3D99F6} 5-4c = 0 c = 5 4 \implies c = \frac 54 , y = 2 5 4 1 ± 0 2 = 3 4 y = \frac {2\cdot \frac 54 - 1 \pm 0}2 = \frac 34 and x = y = 3 2 x = \sqrt y = \frac {\sqrt 3}2 . Implies A B = 3 2 AB = \frac {\sqrt 3}2 and A C B = π 3 \angle ACB = \frac \pi 3 .

Now, the area of the grey area = = area of the parabola for 0 y 3 4 0 \le y \le \frac 34 - area of 2 3 π \frac 23 \pi circular segment of radius 1.

A grey = A parabola A segment = A parabola ( A sector A triangle ) = 2 0 3 4 x d y π 3 + 2 ( 1 2 A B B C ) = 2 0 3 4 y d y π 3 + 3 2 1 2 = 2 2 3 y 3 2 0 3 4 π 3 + 3 4 = 3 2 π 3 + 3 4 = 3 3 4 π 3 \begin{aligned} A_{\text{grey}} & = A_{\text{parabola}} - A_{\text{segment}} \\ & = A_{\text{parabola}} - \left(A_{\text{sector}} - A_{\text{triangle}}\right) \\ & = 2 \int_0^\frac 34 x \ dy - \frac \pi 3 + 2\left(\frac 12 \cdot AB\cdot BC\right) \\ & = 2 \int_0^\frac 34 \sqrt y \ dy - \frac \pi 3 + \frac {\sqrt 3}2\cdot \frac 12 \\ & = 2 \cdot \frac 23 \cdot y^\frac 32 \bigg|_0^\frac 34 - \frac \pi 3 + \frac {\sqrt 3}4 \\ & = \frac {\sqrt 3}2 - \frac \pi 3 + \frac {\sqrt 3}4 \\ & = \frac {3\sqrt 3}4 - \frac \pi 3 \end{aligned}

Therefore, A + B = 3 + 4 = 7 A+B=3+4 = \boxed{7} .

Zico Quintina
May 24, 2018

Let the point ( 0 , a ) (0,a) be the center of the circle. The parabola clearly will intersect the lower half of the circle, which has equation y = 1 x 2 + a y = - \sqrt{1 - x^2} + a .

At the intersection points, the slopes of the tangent lines to the parabola and circle must be equal; to find the intersection points, we equate their derivatives.

d d x ( 1 x 2 + a ) = d d x ( x 2 ) x 1 x 2 = 2 x 1 x 2 = 1 2 [since clearly x 0 ] x = ± 3 2 y = x 2 = 3 4 a = y + 1 x 2 = 5 4 \begin{aligned} \dfrac{d}{dx} (- \sqrt{1 - x^2} + a) &= \dfrac{d}{dx} (x^2) \\ \\ \dfrac{x}{\sqrt{1 - x^2}} &= 2x \\ \\ \sqrt{1 - x^2} &= \dfrac{1}{2} \qquad \small \text{[since clearly } x \not= 0] \\ \\ x = \pm \dfrac{\sqrt{3}}{2} \qquad \implies \qquad y = x^2 &= \dfrac{3}{4} \qquad \implies \qquad a = y + \sqrt{1 - x^2} = \dfrac{5}{4} \end{aligned}

The area between the two curves will then be

- 3 2 3 2 ( 1 x 2 + 5 4 x 2 ) d x = 2 0 3 2 ( 1 x 2 + 5 4 x 2 ) d x = 2 0 3 2 ( 1 x 2 ) d x + 2 0 3 2 ( 5 4 x 2 ) d x = 2 0 π 3 ( 1 sin 2 θ ) cos θ d θ + 2 [ 5 x 4 x 3 3 ] 0 3 2 [In the first integral, substituting x = sin θ , d x = cos θ d θ ] = 2 0 π 3 cos 2 θ d θ + 2 ( 5 3 8 3 8 ) = 2 0 π 3 1 2 ( cos 2 θ + 1 ) d θ + 3 = [ 1 2 sin 2 θ + θ ] 0 π 3 + 3 = ( 3 4 + π 3 ) + 3 = 3 3 4 π 3 \begin{aligned} \int_{\text{-}\frac{\sqrt{3}}{2}}^{\frac{\sqrt{3}}{2}} \left(-\sqrt{1 - x^2} + \dfrac{5}{4} - x^2 \right) dx &= 2 \displaystyle\int_{0}^{\frac{\sqrt{3}}{2}} \left(-\sqrt{1 - x^2} + \dfrac{5}{4} - x^2 \right) dx \\ \\ &= 2 \int_{0}^{\frac{\sqrt{3}}{2}} \left( -\sqrt{1 - x^2} \right) dx \ + \ 2 \int_{0}^{\frac{\sqrt{3}}{2}} \left( \dfrac{5}{4} - x^2 \right) dx \\ \\ &= 2 \int_{0}^{\frac{\pi}{3}} \left( -\sqrt{1 - \sin^2 \theta} \right) \cos \theta \ d\theta \ + \ 2 \left[ \dfrac{5x}{4} - \dfrac{x^3}{3} \right]_{0}^{\frac{\sqrt{3}}{2}} \quad \small \text{[In the first integral, substituting } x = \sin \theta, dx = \cos \theta \ d\theta] \\ \\ &= -2 \int_{0}^{\frac{\pi}{3}} \cos^2 \theta \ d\theta \ + \ 2 \left( \dfrac{5 \sqrt{3}}{8} - \dfrac{\sqrt{3}}{8} \right) \\ \\ &= -2 \int_{0}^{\frac{\pi}{3}} \dfrac{1}{2} \left( \cos 2 \theta + 1 \right) \ d\theta \ + \ \sqrt{3} \\ \\ &= - \left[ \dfrac{1}{2} \sin 2 \theta + \theta \right]_{0}^{\frac{\pi}{3}} \ + \ \sqrt{3} \\ \\ &= - \left( \dfrac{\sqrt{3}}{4} + \dfrac{\pi}{3} \right) \ + \ \sqrt{3} \\ \\ &= \dfrac{3\sqrt{3}}{4} - \dfrac{\pi}{3} \end{aligned}

so A = 3 A = 3 and B = 4 B = 4 giving the answer A + B = 7 A + B = \boxed{7}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...